China’s Partnership with West Africa and Its Implications for Economic Sovereignty - Onome Odokuma; Abraham E. Orhero; Laz Etemike (Journal of Social Science and Humanities, 2026)
This study critically examined China’s expanding influence in West Africa, considering five key states, Nigeria, Ghana, Sierra Leone, Guinea, and Mali, to assess the implications on economic sovereignty. The objectives are to critically assess the implications of China’s expanding influence in West Africa and the implications on economic sovereignty of the sub-region; examine the nature and extent of China’s economic engagement in West African states; and analyse how Chinese investments and infrastructure enhance or undermine the economic sovereignty of West Africa. Adopting a qualitative research design, the paper interrogates how Chinese loans, trade, and infrastructure investments reshape political economy dynamics and strategic dependencies across the sub-region. The method adopted for the study is the historical method relying on the Marxist imperialism and the dependency theories, which revealed a contemporary form of economic imperialism wherein capital accumulation benefits the dominant power while constraining the fiscal and policy autonomy of peripheral states. It was revealed that there is a shift from transactional partnerships to structural influence, positioning China as a development financier stakeholder in the sub-region. Chinese loans and investments have bridged critical infrastructural gaps, especially in energy, transport, and telecommunications. However, these projects are loan-driven and mainly executed by Chinese firms, thereby reinforcing the financial subordination of West African states, especially through capital export for surplus extraction. Multi-polarity has produced a competitive dependency where states oscillate between Chinese, Western, and multilateral financiers without achieving autonomy. West African sovereignty is being redefined, nominally independent but materially constrained as the region becomes a site of accumulation within the global capitalist order dominated by emerging powers like China. The study recommended that ECOWAS must be strategically reinforced to enable collective bargaining with China on major projects. ​West African governments must aggressively pursue diversification strategies, focusing industrial policy on high-value-added exports rather than raw materials.